2013
DOI: 10.1017/s1049023x13008868
|View full text |Cite
|
Sign up to set email alerts
|

Hunger Strikers: Ethical and Legal Dimensions of Medical Complicity in Torture at Guantanamo Bay

Abstract: Physicians and other licensed health professionals are involved in force-feeding prisoners on hunger strike at the US Naval Base at Guantanamo Bay (GTMO), Cuba, the detention center established to hold individuals captured and suspected of being terrorists in the wake of September 11, 2001. The force-feeding of competent hunger strikers violates medical ethics and constitutes medical complicity in torture. Given the failure of civilian and military law to end the practice, the medical profession must exert pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Such potential infringements on autonomy need to be factored into medical assessment. Dougherty et al (2013), in keeping with the position of the World Medical Association ( 2006), note that force-feeding competent hunger strikers may be complicit to torture. It may be worth considering the ethical complexities which may arise for a physician called to conduct the feeding procedure itself.…”
Section: Summary and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Such potential infringements on autonomy need to be factored into medical assessment. Dougherty et al (2013), in keeping with the position of the World Medical Association ( 2006), note that force-feeding competent hunger strikers may be complicit to torture. It may be worth considering the ethical complexities which may arise for a physician called to conduct the feeding procedure itself.…”
Section: Summary and Discussionmentioning
confidence: 85%
“…Caenazzo et al (2016) argue that such conflicts of interest may be avoided by the use of independent 'ethics consultants'. Dougherty et al (2013) argued that personal morals, national security imperatives or military detention were not in themselves sufficient to justify departure from the general principles of medical ethics despite the 'dual loyalty conflict'. No publication in this review suggested a departure from this position, which is in keeping with the Declaration of Malta (World Medical Association, 2006), which notes that 'Physicians with dual loyalties are bound by the same ethical principles as other physicians, that is to say that their primary obligation is to the individual patient … Physicians must remain objective in their assessments and not allow third parties to influence their medical judgement.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The heaviest criticism and subsequent publications have explored physician responsibility to report mistreatment 54 , 55 and handling of life-sustaining treatments, such as “force-feeding” those under hunger strikes. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…The hunger strikes of Bobby Sands and others in the Maze Prison in Belfast, Ireland in the early 1980s are a well-known example; those strikers died after 45–61 days of starvation (33). More recently, waves of hunger strikes have been reported in U.S.-held detainees in the Guantanamo Bay Detention Camp, with controversial force-feeding of these detainees (34). Although uncommon in U.S. prisons, deaths from hunger strikes require an investigation that includes a detailed history from the prison regarding the inmate's statements and actions over the time period in question, interview of other witness inmates for corroboration if possible, and a complete autopsy to include vitreous electrolyte analysis for signs of dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy findings may include muscle wasting, decreased subcutaneous and visceral adipose, and atrophy and decreased weights of organs, including the heart (33, 35). In addition to simple dehydration, hypokalemia is likely to arise with prolonged fasting (34), and may precipitate lethal cardiac arrhythmia. Other mechanisms could include multisystem organ failure or sepsis (35).…”
Section: Discussionmentioning
confidence: 99%